The Influence of Electronic Word of Mouth, Brand Trust, and Product Quality on Purchase Decisions for Glad2Glow Moisturizer - Alif Anggun Yuliasari; Samari; Rino Sardanto (Proceeding International Conference on Digital Education and Social Science, 2025)
This study examines the impact of several elements, namely Electronic Word of Mouth (E-WOM), Brand Trust, and Product Quality on the purchasing decisions of Management students at UNP Kediri, specifically for the class of 2022, regarding Glad2Glow moisturizer products. This study examines each element both individually and in relation to each other. The elements that are the main focus in this study are Electronic Word of Mouth (X1), Brand Trust (X2), and Product Quality (X3). The main objective of this study is to evaluate the impact of these elements on purchasing decisions (Y). The method used in this study is a quantitative approach to understand the relationship between causal factors. The population studied includes all Management students at UNP Kediri, while the sample consists of 40 students from the class of 2022 who have purchased at least one Glad2Glow moisturizer product. Data collection was conducted using an online questionnaire based on a Likert scale. To analyze the data, classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing were conducted. The results showed that Electronic Word of Mouth and Product Quality did not significantly influence purchasing decisions. However, Brand Trust was shown to have a significant impact when analyzed separately. When the three elements were analyzed together, they were found to have a significant influence on purchasing decisions.